PEREMPUAN PUBLIK DALAM NOVEL GADIS KRETEK KARYA RATIH KUMALA: ANALISIS KRITIK SASTRA FEMINIS - , YUDI EKO SAPUTRO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Women in the economic sphere are perceived as being less able to carry out economic functions. This is due to a more dominant role of women in roles that are reproductive. These roles are assessed as non-economic roles. This is evident from the actions of the woman leaning on domestic jobs. In the times, the woman roles in the economic sphere is increasing. It is characterized by the term Wanita Karier (Career Woman) indicating the presence of women's movement in the direction of the public. However, with that things, women are still considered as second-class beings lower than man. Women are less able to dwell in the economic sector. Novel Gadis Kretek works by Ratih Kumala is a novel that elevates women as subjects who are competent in the public affairs. It is characterized by the role of the main character (Dasiyah) in leading and managing kretek company. This study aims to uncover the ideology of equality in the public sphere which camouflaged in the novel . This study examined the socialist feminist approach and qualitative methods as well as the perspective through the concept of Reading as A Woman to produce specific method in the form of opposition figures between kontrafeminis and profeminis in mapping feminist ideas and analysis of the public image of women as the focus analysis. The result is obtained ideology of women equality in the novel. It is economic equality through the ideas which confirmed that the woman is the one who is able to dwell in the realm of production, as well as subjects who are able to act and make strategic decisions and not as a subject confined to domestic affairs.